O futuro das ideias: análise estrutural & incertezas-críticas prospectivas para think tanks - Lima, Marlos Correia de (2010)
The objective of this study is to identify prospective criticai uncertainties for think tanks, important information for the elaboration of prospective scenarios for these organizations. A qualitative approach was adopted. Data were collected from literature and from interviews with key executives from Fundação Getulio Vargas and international specialists were analyzed. A theoretical evaluation of the main think tanks definitions and classifications was performed, and the common elements across the definitions were identified and used to construct a suitable think tank definition that was considered in the subsequent phases of the study. The URCA Structural Analysis Model (MARQUES, 1988) was applied to evaluate 21 prospective variables selected from the collected data. The results indicate 8 prospective criticai uncertainties for think tanks: 1) Think tanks internationalization; 2) Agenda globalization; 3) International projection of the nations; 4) Competition among think tanks; 5) Competition between think tanks and ONGs, advisers, web and other information providers; 6) Technical staff; 7) Leading group; and 8) Financiai diversification and sustainability.